Direct Oral Anticoagulants in Chronic Liver Disease. Issue 10 (October 2019) - Steuber, Taylor D.; Howard, Meredith L.; Nisly, Sarah A.
Objective: To review the use of direct oral anticoagulants (DOACs) in patients with chronic liver disease (CLD).Data Sources: A MEDLINE literature search was performed from 1964 through February 2019 using the following search terms: cirrhosis, chronic liver disease, direct oral anticoagulant, and the individual DOACs.Study Selection and Data Extraction: All English-language human trials and reports that examined DOACs for treatment or prevention of venous thromboembolic (VTE) events in patients with CLD were included.Data Synthesis: A total of 6 clinical trials examining the use of DOACs in patients with CLD were identified. All DOACs have been utilized in patients with CLD, with the exception of betrixaban, for prevention of stroke in atrial fibrillation or treatment of VTE (except for treatment of pulmonary embolism). The studies primarily evaluated patients with mild to moderate liver disease (Child-Turcotte-Pugh class A and B). The DOACs had similar rates of bleeding compared with traditional anticoagulants.Relevance to Patient Care and Clinical Practice: This review evaluates and summarizes the available evidence on DOACs in the setting of CLD. These agents may be more appealing in this population because monitoring or administration may be difficult with traditional anticoagulants (warfarin or low-molecular-weight heparins).Conclusion: Early data suggest that DOACs may be safe in patients with mild to moderate CLD. Should a DOAC be selected as an alternative to traditional anticoagulants, more frequent monitoring should be used because hepatotoxicity may be a concern. Larger clinical trials are needed to address efficacy outcomes as well as differences among individual DOACs in this population.